Effects of Amount, Intensity, and Mode of Exercise Training on Insulin Resistance and Type 2 Diabetes Risk in the STRRIDE Randomized Trials - Ross, Leanna M.; Slentz, Cris A.; Zidek, Alyssa M.; Huffman, Kim M.; Shalaurova, Irina; Otvos, James D.; Connelly, Margery A.; Kraus, Virginia B.; Bales, Connie W.; Houmard, Joseph A.; Kraus, William E. (Frontiers in Physiology, 2021)
Background: Lipoprotein Insulin Resistance Index (LP-IR) and Diabetes Risk Index (DRI) are novel spectroscopic multimarkers of insulin resistance and type 2 diabetes risk. As the STRRIDE randomized trials have previously demonstrated the ability of exercise training to improve traditional markers of insulin action, the aim of this study was to examine the effects of exercise amount, intensity, and mode on LP-IR and DRI. Methods: A total of 503 adults with dyslipidemia [STRRIDE I (n=194), STRRIDE AT/RT (n=139)] or prediabetes [STRRIDE-PD (n=170)] were randomized to control or one of 10 exercise interventions, ranging from doses of 8-23 kcal/kg/week; intensities of 50-75% V̇O2peak; and durations of 6-8 months. Two groups included resistance training and one included dietary intervention (7% weight loss goal). Fasting plasma samples were obtained at baseline and 16-24h after the final exercise bout. LP-IR, DRI, and the branched chain amino acids valine and leucine were determined using NMR spectroscopy. LP-IR and DRI scores range from 0-100 and 1-100, respectively (greater scores indicate greater risk). Paired t-tests determined significance within groups (p<0.05). Results: After training, six exercise groups significantly improved LP-IR (ranging from -4.4 ± 8.2 to -12.4 ±14.1), and four exercise groups significantly improved DRI (ranging from -2.8 ± 8.2 to -8.3 ± 10.4). The most beneficial interventions for both LP-IR and DRI were low amount/moderate intensity aerobic, aerobic plus resistance, and aerobic plus diet. Summary: Multiple exercise interventions improved LP-IR and DRI. In those with dyslipidemia, adding resistance to aerobic training elicited a synergistic effect on insulin resistance and type 2 diabetes risk. In individuals with prediabetes, combining a dietary intervention and weight loss with aerobic training resulted in the most robust type 2 diabetes risk improvement.